Exploring the reactivity of chiral glycidic amides for their applications in synthesis of bioactive compounds. - Sarabia-García, Francisco Ramón; Vivar García, Carlos; García-Ruiz, Cristina; Sánchez-Ruiz, Antonio; Pino-González, María Soledad; García-Castro, Miguel; Chammaa, Samy (Wiley, 2014)
A new class of chiral sulfonium salts, derived from L- and D-methionine, has been designed and successfully employed in our laboratories for the diastereoselective synthesis of glycidic amides. The epoxy amides obtained were converted cleanly into 1,2-difunctionalized products through oxirane ring-opening reactions with different types of nucleophiles. The resulting ring-opened products represent valuable and useful building blocks for the synthesis of different bioactive products. Thus, the expedient synthesis of clavaminol H as well as the synthesis of key precursors for other bioactive compounds, for example, polyketide-derived natural products, have been achieved, demonstrating the synthetic efficiency and utility of this chemistry.
https://openpolicyfinder.jisc.ac.uk/id/publication/1692
Keywords: Compuestos bioactivos; Synthetic methods; Nucleophilic substitution; Diastereoselectivity; Sulfonium salts; Glycidic amides